Brain-derived neurotrophic factor (BDNF): an effect biomarker of neurodevelopment in human biomonitoring programs - Rodríguez-Carrillo, Andrea; Verheyen, Veerle J.; Van Nuijs, Alexander L. N.; Fernández, Mariana F.; Remy, Sylvie (Frontiers in Toxicology, 2024)
The present narrative review summarizes recent findings focusing on the role of brain-derived neurotrophic factor (BDNF) as a biomarker of effect for neurodevelopmental alterations during adolescence, based on health effects of exposure to environmental chemical pollutants. To this end, information was gathered from the PubMed database and the results obtained in the European project Human Biomonitoring for Europe (HBM4EU), in which BDNF was measured at two levels of biological organization: total BDNF protein (serum) and BDNF gene DNA methylation (whole blood) levels. The obtained information is organized as follows. First, human biomonitoring, biomarkers of effect and the current state of the art on neurodevelopmental alterations in the population are presented.Second, BDNF secretion and mechanisms of action are briefly explained. Third, previous studies using BDNF as an effect biomarker were consulted in PubMed database and summarized. Finally, the impact of bisphenol A (BPA), metals, and non-persistent pesticide metabolites on BDNF secretion patterns and its mediation role with behavioral outcomes are addressed and discussed. These findings were obtained from three pilot studies conducted in HBM4EU project. Published findings suggested that exposure to some chemical pollutants such as fine particle matter (PM), PFAS, heavy metals, bisphenols, and nonpersistent pesticides may alter circulating BDNF levels in healthy population. Therefore, BDNF could be used as a valuable effect biomarker to investigate developmental neurotoxicity of some chemical pollutants.